Inveighing Against Inequity: Re-Reading Niranjan Mohanty’s Poetry of Protest: Exploring the Voice of Protest in Niranjan Mohanty's Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Thomas Paine in the Rights of Man and Common Sense points out that every individual’s duty is “to allow the same rights to others as we allow ourselves” and the failure to do so gives birth to social injustice. The Indian freedom fighters cherished the dream of a free India where equality and justice would reign supreme. India achieved freedom, but the dream of social equality and justice for all, still remains unrealized, be it women in particular or the common masses or nature. There is continuous exploitation every now and then. Niranjan Mohanty, the Orissan poet inveighs against such inequity prevalent in the society. This paper seeks to bring out and analyse the voice of protest in Mohanty’s poems like Prayers to Lord Jagannatha, “Near the Temple”, “Kalahandi”, “The World”, “Taming”, “Bhubaneswar” etc.“Whatever is my right as a man is also the right of another and it becomes my duty to guarantee as well as to possess.” ----Thomas Paine